2010
DOI: 10.3390/md8010091
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Photodynamic Therapy: Study of Bacterial Recovery Viability and Potential Development of Resistance after Treatment

Abstract: Antimicrobial photodynamic therapy (aPDT) has emerged in the clinical field as a potential alternative to antibiotics to treat microbial infections. No cases of microbial viability recovery or any resistance mechanisms against it are yet known. 5,10,15-tris(1-Methylpyridinium-4-yl)-20-(pentafluorophenyl)-porphyrin triiodide (Tri-Py+-Me-PF) was used as photosensitizer. Vibrio fischeri and recombinant Escherichia coli were the studied bacteria. To determine the bacterial recovery after treatment, Tri-Py+-Me-PF (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
219
1
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 357 publications
(236 citation statements)
references
References 62 publications
4
219
1
12
Order By: Relevance
“…specifically against cell-wall, virus polymerase or protease) has inevitably led to the emergence of resistant clones, thus becoming a global threat (Bacon et al 2003;Coen and Whitley 2011;Cortez et al 2011;Memoli et al 2011). Due to ROS-mediated targeting of microbial membranes, membrane proteins, DNA, etc., of various pathogens, PACT represents a broad-spectrum multitargeted approach with very limited, if any, chances for the development of resistant bacteria or viruses (Jori et al 2006, Tavares et al 2010Costa et al 2012b;Dosselli et al 2012;Maisch 2015). PACT has been applied successfully to inactivate bacteria, fungi, protozoans and parasites, especially in topical applications such as skin wounds (burns and diabetic foot ulcers) or oral infections (periodontitis and root canal infections) (Tim 2015).…”
Section: Photodynamic Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…specifically against cell-wall, virus polymerase or protease) has inevitably led to the emergence of resistant clones, thus becoming a global threat (Bacon et al 2003;Coen and Whitley 2011;Cortez et al 2011;Memoli et al 2011). Due to ROS-mediated targeting of microbial membranes, membrane proteins, DNA, etc., of various pathogens, PACT represents a broad-spectrum multitargeted approach with very limited, if any, chances for the development of resistant bacteria or viruses (Jori et al 2006, Tavares et al 2010Costa et al 2012b;Dosselli et al 2012;Maisch 2015). PACT has been applied successfully to inactivate bacteria, fungi, protozoans and parasites, especially in topical applications such as skin wounds (burns and diabetic foot ulcers) or oral infections (periodontitis and root canal infections) (Tim 2015).…”
Section: Photodynamic Antimicrobial Activitymentioning
confidence: 99%
“…Photodynamic antimicrobial chemotherapy (PACT) is a possible remedy as it proved to be effective against methicillinresistant Staphylococcus aureus (MRSA) and other multiresistant bacteria (Maisch 2015). Moreover, there is no evidence for the development of resistance to PACT, and such resistance is considered highly improbable, because the oxidative stress in PACT is initiated by a PS that is usually present at multiple cellular sites (Tavares et al 2010;Maisch 2015). Similarly, PDT attacks tumours by causing oxidative damage to different cellular components, and even though there are some examples of resistance to PDT, evidence of resensitisation and synergy in chemoresistant tumour cell lines support the notion that PDT could play an important role in overcoming cancer drug resistance (Spring et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Without irradiation, photosensitizer does not exert cytotoxic effect, indicating that residual toxicity after the treatment is negligible. Furthermore, it is suggested that the PDT does not induce bacterial resistance because singlet oxygen oxidize bacterial cell components non-selectively [26,27]. This is a major advantage in comparison with antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…These ROS will react with many cellular components that will induce oxidative processes leading to cell death (Bonnett 2000, Maisch 2009, Ergaieg et al 2008, Tavares et al 2011, Costa et al 2013, Wainwright et al 2017. The great advantage of this methodology is the unlikelihood of the microorganisms to develop resistance mechanisms since there is not a particular target in the cell and also the PS don't have to accumulate in its interior to be efficient (Dahl et al 1989, Tavares et al 2010, Costa et al 2011a, Preuß et al 2013, Alves et al 2014a.…”
Section: Antimicrobial Photodynamic Inactivation (Pdi) Hasmentioning
confidence: 99%
“…The light output from these bioluminescent bacteria is a highly sensitive marker of their metabolic activity and it can be easily read in a luminometer with a strong correlation between bioluminescence (measured in relative light units, RLU) and viable cell counts. (Tavares et al 2010, Alves et al 2011a, b, Mesquita et al 2014b. The efficiency of the At 20 µM, corroles 2b and 3b were able to reduce A. fischeri bioluminescence of > 6 log 10 RLU after 30 min of irradiation (0.18 kJ cm -2 ) and the results were not significantly different from the pattern of Tetra-Py + -Me (data not shown).…”
Section: Antibacterial Activitymentioning
confidence: 99%